Glycolysis, lipolysis and proteolysis in raw sheep milk Tulum cheese during production and ripening: Effect of ripening materials - Tekin, Ali; Guler, Zehra (Elsevier Sci Ltd, 2019)
In this study, variations in basic chemical constitutes, organic acids (OAs), free amino acids (FAAs) and free fatty acids (FFAs) during ripening of raw sheep's milk Tulum cheeses in goat's skin bag (GST) or plastic barrel (PBT) were investigated. Ripening in goat's skin caused the differences in chemical compositions of Tulum cheese. Moisture loss, salt-in-moisture, fat and protein contents increased. No residual lactose was observed after 90 day. Lactic acid was principal organic acid, followed by propionic acid, acetic acid, formic acid, succinic acid and citric acid. The majority of amino acids were composed of Val, Pro, Tyr, Met, Leu, Trp, Phe, Lys and Glu. Hexadecanoic acid was the most abundant free fatty acid in the cheeses, which followed by cis-9-octadecenoic, octadecanoic, tetradecanoic, decanoic and trans-9-octadecenoic acids. The levels of total FFA and total OA were higher in GST-cheese in comparison to PBT-cheese but total FAAs were lower.
Keywords: Tulum cheese; Ripening material; Glycolysis; Lipolysis; Proteolysis